2017
DOI: 10.1016/j.intimp.2016.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Irbesartan ameliorates hyperlipidemia and liver steatosis in type 2 diabetic db/db mice via stimulating PPAR-γ, AMPK/Akt/mTOR signaling and autophagy

Abstract: Irbesartan (Irb), a unique subset of angiotensin II receptor blockers (ARBs) with PPAR-γ activation function, has been reported to play a role in renal dysfunction, glucose metabolism, and abnormal lipid profile in diabetic animal models and humans. However, the underlying mechanisms that improve hyperlipidemia and liver steatosis are unclear. This study investigated the effects of Irb on lipid metabolism and hepatic steatosis using the spontaneous type 2 diabetic db/db mouse model. The results demonstrated bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 44 publications
3
39
1
Order By: Relevance
“…We identified 421 potential genes in the miRNA databases. On the basis of prior studies addressing mTOR and FOXO1 in regulating dyslipidemia (Houde et al, ; Sajan et al, ; Zhong et al, ), we hypothesized their major roles played downstream of miR‐96 (Data S6: miR‐96 predicted target score, mTOR: 98, FOXO1: 75, Atg16l1: 81, Atg9a: 55). Western blotting was performed to compare the protein levels of mTOR, p‐mTOR (ser2448), FOXO1, LC3A/B, P62, and Beclin‐1 in the liver (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…We identified 421 potential genes in the miRNA databases. On the basis of prior studies addressing mTOR and FOXO1 in regulating dyslipidemia (Houde et al, ; Sajan et al, ; Zhong et al, ), we hypothesized their major roles played downstream of miR‐96 (Data S6: miR‐96 predicted target score, mTOR: 98, FOXO1: 75, Atg16l1: 81, Atg9a: 55). Western blotting was performed to compare the protein levels of mTOR, p‐mTOR (ser2448), FOXO1, LC3A/B, P62, and Beclin‐1 in the liver (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…PPARγ is the most extensively studied. Some ARBs can activate PPARs and have been widely recognized [173][174][175][176][177]. Current research shows PPARs and AMPK are also closely related.…”
Section: Pparsmentioning
confidence: 99%
“…Previous studies have shown that the activation of PPARγ has bene cial effects on the level of autophagy [27]. To further explore the role of PPARγ in O 3 -induced autophagy, chondrocytes were treated with the PPARγ inhibitor GW9662 before ozone treatment.…”
Section: Discussionmentioning
confidence: 99%